2020
DOI: 10.1111/dmcn.14612
|View full text |Cite
|
Sign up to set email alerts
|

Motor imagery and action observation for predictive control in developmental coordination disorder

Abstract: In 2019, international clinical practice recommendations on the definition, diagnosis, assessment, intervention, and psychosocial aspects of developmental coordination disorder (DCD) were published. Informing our understanding of mechanisms, recent systematic reviews have shown that children with DCD have difficulties with the predictive control of movements, including aspects of motor planning, which is expressed as the internal modeling deficit hypothesis. This motor control deficit is most evident when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Consistent with this view, completely novel movements for which no internal motor representation exists cannot be learned with motor imagery alone [6,109]. For novel or otherwise poorly represented actions, a better approach might be to use action observation to help build internal representations [110,111], which can then be strengthened with motor imagery.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with this view, completely novel movements for which no internal motor representation exists cannot be learned with motor imagery alone [6,109]. For novel or otherwise poorly represented actions, a better approach might be to use action observation to help build internal representations [110,111], which can then be strengthened with motor imagery.…”
Section: Methodsmentioning
confidence: 99%
“…Barhoun et al, 2021Barhoun et al, , 2019Deconinck et al, 2009;Noten et al, 2014;Reynolds et al, 2015;Williams et al, 2008;Wilson et al, 2004). Children with DCD can make proper use of instructions to improve their motor imagery abilities (Reynolds et al, 2015;Williams et al, 2008), and motor imagery training has been shown helpful for motor control remediation in DCD (Steenbergen et al, 2020), again attesting that internal models can be updated. Overall, deficits in DCD therefore seem to affect different components of internal models, making it difficult to decipher the core neurocognitive deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Barhoun et al, 2019Barhoun et al, , 2021Deconinck et al, 2009;Noten et al, 2014;Reynolds et al, 2015;Williams et al, 2008;Wilson et al, 2004). Children with DCD can make proper use of instructions to improve their motor imagery abilities (Reynolds et al, 2015;Williams et al, 2008), and motor imagery training has been shown helpful for motor control remediation in DCD (Steenbergen et al, 2020), again attesting that internal models can be updated. Overall, deficits in DCD therefore seem to affect different components of internal models, making it difficult to decipher the core neurocognitive deficit.…”
Section: Introductionmentioning
confidence: 99%